Communication Strategy Fashion Luxury Brand in Increase Brand Experience with among Millennials in the Time of the COVID-19 Pandemic: A Systematic Literature Review - Tiara Angelica Tarigan; Irwansyah Irwansyah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Literature review systematic this conducted for see trend related research with literature utilization implementation of communication strategy fashion luxury brand in increase brand experience to circles Millennials during the COVID -19 pandemic. 9 literatures on the range time 2021-2022 reviewed use method systematic literature review (SLR) for answer destination research. Studies this find that digital marketing is tool important for communicate brand luxurious market leading for circles millennial. Build digital relationship like via social media with consumer effect on intentions buy for luxury fashion brand. If brand could create designed marketing with good for their target audience, they could produce equity brand based on strong customer with give satisfying brand experience.